2020
DOI: 10.1111/codi.14938
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of radiologically enlarged lymph nodes in node‐negative colon cancer

Abstract: Aim Assessment of lymph node (LN) involvement is of crucial importance in the estimation of prognosis and choice of therapeutic options for patients with colon cancer. The relationship between the radiological size of LNs and prognosis in node-negative colon cancer remains uncertain. This study aims to investigate the prognostic impact of radiologically enlarged LNs on the survival of patients with node-negative colon cancer.Method This retrospective study recruited 395 patients with Stages I and II colon canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Patients with enlarged rLN had poor DFS and OS because of micrometastasis of these LNs. 21 Bruno and his colleagues demonstrated that node‐negative colon cancer with more than seven enlarged LN (>5 mm) had a significantly better outcome comparing those without. 22 These contrasting results showed that the prognostic value of LN in colorectal cancer remained unclear and additional studies with a larger sample size were necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with enlarged rLN had poor DFS and OS because of micrometastasis of these LNs. 21 Bruno and his colleagues demonstrated that node‐negative colon cancer with more than seven enlarged LN (>5 mm) had a significantly better outcome comparing those without. 22 These contrasting results showed that the prognostic value of LN in colorectal cancer remained unclear and additional studies with a larger sample size were necessary.…”
Section: Discussionmentioning
confidence: 99%
“…One study of our center had reported that the enlarged rLN was a risk factor in colon cancer. Patients with enlarged rLN had poor DFS and OS because of micrometastasis of these LNs 21 . Bruno and his colleagues demonstrated that node‐negative colon cancer with more than seven enlarged LN (>5 mm) had a significantly better outcome comparing those without 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Murphy et al 15 and Okada et al 16 reported that among patients with colon cancer pathologically diagnosed as negative for LN metastasis (pathological N0, pN0), those with enlarged LNs had a better prognosis than those without enlarged LNs. However, Song et al 18 reported that enlarged LNs were correlated with a poor prognosis, even in patients with pN0 colon cancer. Therefore, the immunological effect for better prognosis in stage II CRC patients with enlarged LNs remains unelucidated.…”
mentioning
confidence: 99%
“…Previous studies have also shown lymph node follicular hyperplasia in the drainage areas of patients with stage II colon cancer [9], suggesting an association between non-metastatic enlargement of tumordraining lymph nodes and the tumor-adaptive immune response. Recently, some studies have reported that BLNE is a favourable prognostic factor for colorectal cancer [7,10], while other studies have proposed hat it is associated with poorer prognosis [11]. Therefore, the clinical signi cance of mesenteric BLNE in stage I/II CRC with remains unclear.…”
mentioning
confidence: 99%